Chemical Profile and Biological Activities of Essential Oil from Flowers of Artemisia dubia Wall. ex Bess. Growing Wild in Western Himalaya, India - Shameem, Shameem Ahmad; Khan, Khaliquz Zaman; Waza, Ajaz Ahmad; Banday, Abid Hussain; Ramzan, Asiya; Shah, Abdul Hasseb; Ganai, Bashir Ahmad (Asian Journal of Chemistry, 2019)
The flowers of Artemisia dubia wall ex Bess., on hydrodistillation provided a refreshing violet-blue viscous essential oil with sweet woody odour. The oil was found to be a complex mixture of monoterpenes, sesquiterpenes and their esters. A total of 67 chemical constituents comprising 79.43 % of the oil were characterized with the help of gas chromatography and mass spectrometry (GC/MS). Major chemical constituents of the oil were characterized as nerylisovalerate (9.79 %), 1,8-cineole (8.32 %), neryl-2-methyl-butanoate (7.32 %), chamazulene (5.92 %), linalool (4.15 %), camphor (4.10 %), germacrene D (4.04 %), nerol (3.37 %), linalyl propionate (3.32 %). The investigations performed on the flower essential oil of A. dubia allowed the distinction of this plant growing in the temperate Kashmir region of western Himalayas from the same plant with different varieties growing in different parts of the world. The essential oil was evaluated for its antifungal activity against Candida species and was found to be active against the tested strains with more sensitivity against C. paropsilosis and C. krusei strains. The antioxidant activity evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and thiobarbituric acid reactive substances (TBARS) assay evidenced that the essential oil has moderate antioxidant activity. The antiproliferative ability of the oil was evaluated by MTT assay against the two cell lines A549 (human lung adenocarcinoma epithelial cells) and HCT-116 (human colon cancer cells). The essential oil effectively inhibits the growth of A549 and HCT-116 cancer cells at 62.5 and 31.25 μg/mL concentration, respectively.